Has German business income taxation raised too little revenue over the last decades? - Stefan Bach (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This study presents comprehensive macroeconomic measures on the revenue from business taxation in Germany. A comparison of the tax base reported in tax statistics with the corporate income derived from national accounts gives hints to considerable tax base erosion. The high weight of reported tax losses underlines this result. The average implicit tax rate on corporate income was around 21 percent since 2001, and thus falling considerably short of statutory tax rates and effective tax rates discussed in the literature. For lack of detailed accounting data it is hard to give precise reasons for the presumptive tax base erosion.
Keywords: H25; H26; H22; 330; business income taxation; implicit tax rates; tax base erosion